Load simulation analysis of a new erection system based on the gas-assisted drive erecting scheme. Issue 1 (January 2021) - Wu, Qipeng; Ma, Cong; Li, Liang; Yang, Minbo
Abstract: To improve the traditional erecting process with lower velocity and smaller power density, a new erection system is designed based on the hybrid drive of gas and electric cylinder, witch could erect quickly without increasing the power of the whole machine. According to the prescribed rotational motion and the rotational differential equation of the erection mechanism, the computational models of the related characteristic parameters in erection process were set up. Taking some parameters of a missile as boundary conditions, the models were simulated in MATLAB, and the parameters were obtained graphically. The results can offer references for the design of a new erection mechanism based on pyrotechnics.